Response to ‘Brexit, Archaeology and Heritage: Reflections and Agendas’ - Lorna-Jane Richardson; Tom Booth (Papers from the Institute of Archaeology, 2017)
This research was presented at the UCL Brexit, Archaeology and Heritage workshop and here it is summarised as a response to the lead forum article ‘Brexit, Archaeology and Heritage: Reflections and Agendas’.
Keywords: Nation; Heritage; Digital Social Research; Archaeology; National Identity; Brexit; DNA; Big Data